Leadership as a situated practice: Critical connections and liberated networks - Buckley, Carina (Journal of University Teaching and Learning Practice, 2024)
Learning Development is founded on multidisciplinary partnerships and collaboration, which can make it difficult for practitioners to recognise leadership in themselves and have it recognised by others, stymieing progression and confidence. This study aims to explore what leadership looks like in a collaborative, community-driven, third space field of practice, and how Learning Development practitioners might recognise leadership in themselves and enact it in practice. Based on based on semi-structured interviews, a phenomenological approach is taken to explore the perceptions and experiences of 20 participants who self-identify as Learning Developers with an interest in leadership. Four key themes emerged from the analysis: Being in the role; Being part of a team; Being part of a community; and Taking a wider view. Each indicates how leadership in Learning Development is values-driven, social, networked, critical, and operates on the three levels of team, community, and field. The interrelationships between these are expressed as a model for strategic influence driven by collaborative connections, and findings suggest that practitioners act as a hub through which knowledge and connections can flow. Given the challenges currently facing the higher education sector, it is vital that institutions are able to harness these crucial roles to remain flexible, responsive, and effective. This study provides a means for recognition and advancement in fields that lack the clear progression routes of academic and professional services colleagues.